Pengaruh Model Pembelajaran Inkuiri Terhadap Hasil Belajar Peserta Didik Pada Tema Panas Dan Perpindahannya Kelas V SD Negeri 040457 Berastagi - Tiodora Br Tarigan; Regina Sipayung; Bogor Lumbanraja; Rumiris Lumban Gaol; Juliana Juliana (Departement of Mathematics Education, 2023)
This study aims to determine the effect of the inquiry learning model on student learning outcomes in class V of SD Negeri 040457 Berastagi in the 2022/2023 Learning Year. In this study, researchers used quantitative methods. The population of this study were all students in class V of SD Negeri 040457 Berastagi totaling 31 students. The sample used in this study was saturated sampling in this case all members of the population were used as samples totaling 31 students. The results of this study indicate that the results obtained from correlation testing can be seen in the correlation coefficient of rcount (0.716) > rtable (0.355), it can be concluded that the alternative hypothesis (Ha) is accepted, namely that there is a positive and significant influence between the inquiry learning model on the learning outcomes of students on the theme of heat and its transfer in class V of SD Negeri 040457 Berastagi. It can also be seen from the results of the t test where tcount> ttable is 5.531> 1.699, then Ha is accepted. This shows that there is a significant positive effect between the inquiry learning model on the learning outcomes of students on the theme of heat and its transfer in class V of SD Negeri 040457 Berastagi in the 2022/2023 academic year.